EMPOWERMENT OF WOMEN IN MODERN SOCIETY (International Journal of Food and Nutritional Sciences, 2022)
Hillary Clinton- “When women are held back, our country is held back. When women get ahead, everyone gets ahead.” Women, adult and child are treated as weaker in the society so they need special attention. The Indian society is multilingual as well as multireligious and follow various culture and traditions. This paper is regarding women’s rights which are violated frequently in every phase of their life Women suffers in silence and deprived of their basic rights in the patriarchal society, Human rights are rights granted to every individual without any discrimination on grounds of religion, race, caste, sex. In this paper an attempt has been made to study the human rights of women in India i.e. how rights of women are protected by various legislations and initiative of government. There exists a huge gap between de jure and de facto rights of women due to practices prevalent and structure of Indian society.Keywords: Multicultural, Universal Declaration of Human Rights, Violation of Rights, Legislations etc.